Pengaruh Manfaat, Kemudahan, dan Pendapatan terhadap Minat Menggunakan Paylater: Studi Kasus Masyarakat di DKI Jakarta - Hasanah Jaya Asja; Santi Susanti; Achmad Fauzi (Penerbit Goodwood, 2021)
Purpose: This study examined the influence of perceived usefulness, ease of use, and income on interest in using paylater services. Research Methodology: The population in this study was the people of DKI Jakarta who know the Shopee Paylater service. The research sample was obtained using a purposive sampling method, with an affordable population calculation obtained 400 samples. The research method used was a quantitative method with multiple regression models. Data were primary data obtained from distributing questionnaires. Results: The results of the study partially show that perceived usefulness has a positive and significant influence on the interest of using paylater services; perceived ease of use has no positive and significant influence on interest of using paylater services; and income has a positive and significant influence on interest of using paylater services. Limitations: It is necessary to investigate other variables that can affect interest in using paylater services. Contribution: E-commerce companies should develop factors that influence consumer interest in using paylater and increase consumer knowledge before using paylater services. Keywords: Perceived Usefulness, Perceived Ease of Use, Income, Intention of Using Paylater